12‐1: Analysis of Key Factors Affecting the Lifetime of Blue Phosphorescent OLED Using CN Modified Blue Host Materials. Issue 1 (29th May 2019) - Yang, Chang Yoon; Jang, Ho Jin; Lee, Kyung Hyung; Byeon, Sung Yong; Lee, Jun Yeob; Jeong, Hyein
Abstract : Three host materials were synthesized for blue phosphorescent organic light emitting diodes (OLEDs) by combining carbazolylcarbazole and benzonitrile. Each material has different CN positions relative to the carbazolylcarbazole donor as ortho, ‐meta, and para. These materials were used for finding fundamental factors of lifetime degradation of blue OLEDs. By comparing the characteristics of the three hosts with the CN unit at ortho, meta and para positions, we studied the effects of the CN position on the lifetime of the blue phosphorescent OLEDs. We calculated bond dissociation energy of the three hosts and energy transfer to find key factors about degradation. We calculated Forster energy transfer rate from host to dopant by measuring parameters for the calculation. The correlation of the device lifetime with the parameters revealed that the bond dissociation energy and Forster energy transfer rate are critical to the device lifetime of the blue phosphorescent OLEDs.